Effect of QR-Code-Based Learning Media on Civics Achievement in Indonesian High Schools - Arfah, Wahyudin; Suardi, Suardi; Mutiara, Indah Ainun; Hashim, Shahrin Bin (Universitas Muhammadiyah Makassar, 2025)
The urgency of this research arises from the persistently low learning achievement in Pancasila and Citizenship Education (PPKn) in Indonesian senior high schools, which is partly attributable to the suboptimal integration of digital technology into classroom instruction. This study aims to examine the effect of QR-code-based learning media on students’ PPKn learning achievement at SMA Negeri 2 Gowa, Bajeng District, Gowa Regency. A quantitative approach with a quasi-experimental, nonequivalent control group design was employed. The population comprised all grade XI students in the 2024/2025 academic year, with two classes selected as samples: XI-A as the experimental group and XI-B as the control group (32 students in each class). Data were collected through learning achievement tests, questionnaires, and interviews, and were analyzed using an independent samples t-test and N-Gain score. The findings indicate that the use of QR-code-based learning media significantly improves students’ PPKn achievement, with learning gains falling in the medium to high categories based on N-Gain analysis. Questionnaire data further reveal that students respond positively to QR-code media, perceiving it as engaging, practical, and supportive of independent access to learning materials. These results lead to the conclusion that QR-code-based learning media is an effective and feasible alternative for enhancing PPKn achievement in the digital era. The novelty of this study lies in the systematic integration and evaluation of QR-code technology specifically within PPKn instruction at the senior high school level. This research contributes theoretically by enriching the literature on technology-enhanced civic education and practically by providing an evidence-based model of innovative digital media for classroom implementation.